2022
DOI: 10.1186/s12909-022-03113-3
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrics and gynecology resident perception of virtual fellowship interviews

Abstract: Background Travel restrictions amidst the COVID-19 pandemic reshaped interviewing for fellowships into a predominantly virtual process. How this impacts Obstetrics and Gynecology (OB/GYN) resident approaches to fellowship application and Match navigation is largely unknown. Methods We performed a cross-sectional survey study of fourth year OB/GYN residents in the United States who participated in at least one virtual fellowship interview in 2020. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 5 publications
(2 reference statements)
3
17
0
Order By: Relevance
“…[ 13 ] Ding et al also surveyed applicants to multiple subspecialities and found strengths of the virtual platform included cost savings and ease of scheduling interviews but noted uncertainty in ability to create a rank list. [ 17 ] Our larger and broader study corroborates some of their findings, including the clear financial benefit, but found virtual interviews to be adequate in creating a rank list.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…[ 13 ] Ding et al also surveyed applicants to multiple subspecialities and found strengths of the virtual platform included cost savings and ease of scheduling interviews but noted uncertainty in ability to create a rank list. [ 17 ] Our larger and broader study corroborates some of their findings, including the clear financial benefit, but found virtual interviews to be adequate in creating a rank list.…”
Section: Discussionsupporting
confidence: 79%
“…The anticipated expenses of in-person interviews were similar to those reported by other specialties. [ 2 , 4 , 17 , 20 ] Nearly all applicants cite the dramatic reduction in actual expenses for virtual interviews as a significant advantage. Tseng et al found that fellowship candidates during COVID 19 saved close to $6,000 in interview travel expenses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Existing studies on the 2020-2021 virtual application process surveyed applicants before interviews occurred, asked residents in the context of fellowship applications, or assessed how faculty viewed virtual interviews. [4][5][6][7][8][9][10] While studies indicate that fellowship program directors prefer in-person interviews, residents applying for fellowship expressed mixed opinions about whether virtual interviews should continue. [5][6][7][8][9][10] Fellowship applicants noted the financial and time benefits of virtual interviews but expressed concerns with evaluating fit.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] While studies indicate that fellowship program directors prefer in-person interviews, residents applying for fellowship expressed mixed opinions about whether virtual interviews should continue. [5][6][7][8][9][10] Fellowship applicants noted the financial and time benefits of virtual interviews but expressed concerns with evaluating fit. [5][6][7][8] A comprehensive evaluation of a virtual Match process requires input from all stakeholders, including applicants to residency positions.…”
Section: Introductionmentioning
confidence: 99%